Small Unruptured Intracranial Aneurysms Can Be Effectively Treated With Flow-Diverting Devices - Li, Li; Gao, Bu-Lang; Shao, Qiu-Ji; Zhang, Guang-Lin; Wang, Zi-Liang; Li, Tian-Xiao; Zhu, Liang-Fu (Frontiers in Neurology, 2022)
Purpose: To investigate the effect and safety of flow diverters in the management of small (<10 mm in diameter) unruptured intracranial aneurysms. Materials and methods: One hundred and ten patients with 145 small intracranial aneurysms treated with flow diverters were retrospectively enrolled. The clinical, endovascular and follow-up data were analyzed. Results: One hundred twenty-one flow diverters were deployed for the treatment of 145 small intracranial aneurysms in 110 patients, and the stenting success rate was 99.1%. In 133 (91.7%) aneurysms, only flow diverting devices were deployed, and in the rest 12 (8.3%) aneurysms, coils were used to loosely pack the aneurysm after deployment of thea flow diverting device. Five patients (4.5%) experienced ischemic complications, but no hemorrhagic complications occurred. All patients had clinical follow-up 6-18 (median 12) after the procedure, with the mRS 0 in 101 patients, 1 in four, 2 in three, 4 in one, and 5 in one. Digital subtraction angiography was performed at follow-up in 90 (81.8%) patients with 118 (81.4%) aneurysms 6-18 months (median 12) after the procedure, with the Raymond grade I in 90 (76.2%) aneurysms and Raymond grade III in 28 (23.7%). Eighteen patients with 22 partially-occluded aneurysms at the first angiographic follow-up experienced the second digital subtraction angiography 12-36 months (median 26) after the procedure, and 21 (95.5%) aneurysms were completely occluded. Two patients had asymptomatic instent stenosis. Conclusion: Treatment of small unruptured intracranial aneurysms with flow diverters can be performed safely and effectively with satisfactory outcomes